The Electrophysiological Features in X-Linked Charcot-Marie-Tooth Disease With Transient Central Nervous System Deficits - Wen, Qingxian; Cao, Longqiao; Yang, Cun; Xie, Yanchen (Frontiers in Neurology, 2018)
Abstract: Background: Electrophysiological examination plays an important role in the diagnosis of X-linked Charcot-Marie-Tooth (CMTX1) with transient central nervous system deficits. However, electrophysiological features in these diseases are seldom reported. Methods: We reviewed and analyzed the published reports to determine the electrophysiological features of CMTX1 patients with transient central nervous system deficits. Results: A total of 21 CMTX1 patients with transient central nervous system deficits were found in 17 published case reports/series. The age of onset ranged from 0.5 to 18 years old with a mean age of 12.02 ± 0.78 years old. All patients were male. Recurrent episodes of central nervous system deficits were reported in all 21 cases and resolved in several minutes to 3 days. All 20 patients who had MRIs at presentation had bilaterally symmetrical abnormal T2/Diffusion signal in the white matter without enhancement of gadolinium. All subsequent showed improvement or were within normal limits. The median motor nerve conduction velocity (MNCV), motor latencies, and compound muscle action potentials (CMAP) amplitude were the most commonly measurable electrophysiological parameters (85.7%). All cases that had MNCV at presentation had slower and significantly decreased MNCV compared with the normal value (34.1±1.10 m/s vs 46.8±2.05 m/s, P < 0.0001; 95% CI -17.4 to -7.92). The average variation of MNCV in median nerve, ulnar nerve, peroneal nerve and tibial nerve were 22.0% ± 5.96%, 27.6% ± 11.9%, 25.9% ± 4.36%, 27.3% ± 4.30%, respectively. All cases that had Sensory Nerve Conduction Velocity (SNCV) at presentation had slower and significantly decreased SNCV compared with the normal value (35.3±1.33 m/s vs 47.7±2.40 m/s, P < 0.001; 95% CI -18.2 to -6.46). The average variation SNCV in median nerve, ulnar nerve and sural nerve were 19.9% ± 8.24%, 25.2% ± 7.75% and 23.2% ± 3.95%, respectively. Conclusion: This case series serves as a reminder that electrophysiological examination should be included in the diagnosis of recurrent and episodic neurological deficit with white matter lesion. Median MNCV is a sensitive and valuable parameter to support the diagnosis of CMTX1 with transient central nervous system deficits.